Significant predictors of success and non-completion in first year accounting at a South African university - Joubert, J. A. (University of the Free State, 2010)
The main purpose of the research study was to determine significant predictors of success and non-completion in first-year accounting. In order to do so, cognitive as well as non-cognitive factors that may have an influence on performance in firstyear accounting were identified through a literature study, and relatively unexplored factors were identified. Therefore, the research study investigated whether study attitude, abstract thinking and time perspective can statistically predict performance in first-year accounting. A quantitative non-experimental predictive multivariate design was used and confounding variables were taken into consideration. Five hundred and thirty three (533) first-year accounting students at a South African University participated in the study. The participants completed the Psycho-Social Questionnaire (PSQ), factor B of the 16PF Questionnaire, and the Zimbardo Time Perspective Inventory (ZTPI). Study attitude was measured in terms of performance in another first-year subject that most of the first-year accounting students had to enrol for. A univariate analysis indicated significant relationships between achievement in first-year accounting and age, gender, psychosocial background, past-negative time perspective and study attitude. The results also indicated that the relationship between first-year accounting and abstract thinking ability is not statistically significant because the sample scores for abstract thinking ability were homogeneously grouped around the mean. Because factors that may have an influence on performance in accounting are interrelated, a multivariate analysis indicated significant relationships between performance in first-year accounting and age, the past-negative time perspective and study attitude. Therefore, the above-mentioned factors can predict performance in first-year accounting to a certain extent. The most outstanding result of the study was that a past-negative time perspective together with an unfavourable psychosocial background may lead to non-completion in first-year accounting.
Keywords: Thesis (Ph. D. (Higher Education Studies))--University of the Free State, 2010; Accounting -- Study and teaching (Higher) -- South Africa; Multivariate analysis; Univariate analysis; Psychosocial background; Past-negative time perspective; Abstract thinking; Study attitude; Success; Non-completion; Non-cognitive; Cognitive; Time perspective